Development of EST-SSR markers for Taxus cuspidata from publicly available transcriptome sequences. (December 2015) - Ueno, Saneyoshi; Wen, Yafeng; Tsumura, Yoshihiko
Abstract: Simple sequence repeats (SSRs) from a public database were surveyed to identify potential EST-SSR markers for Taxus cuspidata . A total of 5.4 gigabase pairs of RNA-sequencing data were downloaded and assembled into 179, 687 contigs, 7404 (4.1%) of which contained SSR sequences. One hundred and fifty PCR primer pairs were designed for SSRs with repeat numbers ≥9 and screened for variation in 18 T. cuspidata trees. Eighty markers showed length variation, with numbers of alleles and expected heterozygosity ranging from 2 to 11 and 0.056 to 0.907, respectively. These EST-SSR markers are expected to be useful for studying the genetic diversity and conservation of Taxus genetic resources. Highlights: Eighty novel polymorphic microsatellite markers for Taxus cuspidata were developed. These loci were characterized for polymorphisms with 18 individuals of the species. Markers will be useful for the analysis of genetic diversity.